Penerapan Model Pembelajaran Auditory, Intellectually, Repetition (Air) terhadap Hasil Belajar Matematika Siswa - Maria Luthfiana; Reny Wahyuni (Jurnal Pendidikan Matematika:Judika Education, 2019)
This study aims to determine the completeness of mathematics learning outcomes of VIII grade students of SMP Negeri Selangit after applying the Auditory, Intellectually, Repetition (AIR) learning model. The research method, is a quantitative research with quasi-experimental research design (quasi experiment). The sample in this study was grade VIII.4 students consisting of 30 students. Data collection was carried out using test techniques. The test data collected was analyzed using t-test. The results of the study, based on t-test analysis with a significant level α = 0.05, obtained an average test score before the application of the Auditory, Intellectually, Repetition (AIR) learning model was 22.15 and after the application of the Auditory learning model, Intellectually, Repetition (AIR) obtained an average test score of 73.94 with tcount> ttable (2,821)> (1,699). Conclusion, student mathematics learning outcomes after VIII SMP Negeri Selangit after the application of the Auditory, Intellectually, Repitition (AIR) model are significantly completed. Keywords: Auditory, Learning Outcomes, Intellectually, Repetition